Overview of Cannabis including Kampo Medicine and Therapy for Treatment of Dementia: A Review - Wenger, Tibor; Watanabe, Kazuhito; Sasaki, Yui; Kanazawa, Keiko; Shimizu, Koichi; Sirikantaramas, Supaart; Shoyama, Yoshinari; Taura, Futoshi; Morimoto, Satoshi; Shoyama, Yukihiro (Frontiers in Pharmacology, 2022)
Cannabis sativa Linne is belonged to Cannabinaceae, dioecism and annual herb and is the most familiar favorite item using three percent of world population for relaxation in the world. The flower and seed of cannabis were listed in 120 safety medicines of the Chinese book, Shennong’s Classic of Materia Medica called as mafen (written 2 thousand years ago) and the hemp seed is used for Kampo medicine. Among hundred or more cannabinoids tetrahydrocannabinol (THC) and cannabidiol (CBD) are major pharmacologically and psychologically active compounds having affinity against CB1 and CB2 receptors and now approved drugs. Wide investigation for CBD might be developing to anti-dementia drug especially Alzheimer’s disease. The biosynthetic enzymes for cannabinoids were purified, isolated, cloning and the tertiary structure of tetrahydrocannabinolic acid (THCA) synthase was determined by X-ray crystallography. Molecular breeding using biotechnology has been discussed for the efficient production of CBD.